Artificial Intelligence Based Hybrid Forecasting Approaches for Wind Power Generation: Progress, Challenges and Prospects - Lipu M.S.H.; Miah M.S.; Hannan M.A.; Hussain A.; Sarker M.R.; Ayob A.; Saad M.H.M.; Mahmud M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Electric power generation; Stochastic systems; Weather forecasting; Wind power; Activation functions; Generalization performance; Influential factors; Learning capabilities; Performance analysis; Stochastic characteristic; Training algorithms; Wind power forecasting; Electric power transmission networks